Does Antwerp Belong to Everyone?: Unveiling the Conditional Limits to Inclusive Urban Citizenship - Puymbroeck, Nicolas Van (Social Inclusion, 2014)
Recent theoretical discussions have indicated that citizenship is not only a way of being, but also a way of behaving. This article aims to show how attempts to regulate the behaviour of the citizenry can introduce a new topography of inclusion and exclusion, thereby exercising a direct effect on particular ethnic minorities. We investigate the issue in Antwerp, the largest city of the Flemish Region in Belgium. With his slogan ‘Antwerp belongs to everyone’ former mayor Patrick Janssens gained significant international attention for Antwerp’s supposedly inclusive conception of urban citizenship. In this article, we argue that the universality of Antwerp’s city slogan has nevertheless veiled the introduction of new exclusionary prescriptions centred around citizens’ conduct. Drawing on a Foucauldian account of power, three different modes of policing are discussed that have rearticulated the boundaries of urban citizenship in Antwerp. The disciplinary, bio-political and etho-political techniques of power each show in a different way attempts by the state to steer and effectively regulate what counts as appropriate conduct. As a corollary of governmental power, particular ways of behaving have been labelled as deviant and abnormal, thus rendering full citizenship conditional on a set of substantial expectations on how to perform as a citizen. As these expectations are only apparently neutral with respect to ethnic identities, a tension arose between the city’s universal and inclusive rhetoric and its particular and exclusionary policies.